Diagnóstico das condições de saneamento básico dos municípios do Estado de Goiás operados pelas prefeituras - Lima, Aline Souza Carvalho (2014)
Despite all progress made in the areas of environmental sanitation , a large number of people who do not have access to all necessary to promote quality of life components . Thus, this study examined the conditions of sanitation, by calculating the Indicator of Environmental Health ( ISA ) , and consumer satisfaction of 21 municipalities in Goiás operated directly by the City Halls . The methodological process involved the technical visits in all municipalities , application forms with the managers of sanitation systems and consumers as well as secondary data . It was observed that the most deprived areas are related to sewage and solid waste , revealing that most of the municipalities visited not manage these systems properly. In addition , the study noted the lack of water treatment in 33.3 % of the municipalities . As for consumer satisfaction , it was noticed in most of the municipalities visited dissatisfaction precisely in the most deprived areas observed during the calculation of the ISA . In general , all studied municipalities must conform to some health component.